MEDIA SOSIAL INSTAGRAM SEBAGAI SARANA JIHAD - Fathimah Nadia Qurrota A'yun (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2020)
This paper aims at proposing an understanding of the forms of jihad found on Instagram social media. Seeing social media is the current communication trend with rapid development and utilization. One popular social media is Instagram. Instagram can be a means of jihad and alternative propaganda in da'wah. The method used in this article is descriptive qualitative by analyzing the content in posts and caption writing on social media Instagram. The contribution of research is to provide a comprehensive understanding of jihad and show that jihad that is supposed to be is not related to the radical element. Through content analysis, uploads have been found on instagram containing jihad activities in accordance with the indicators of jihad with the Qur’an and Hadis, jihad with property and jihad of passion. This proves that Instagram social media is in fact capable of becoming a means of jihad for the present generation that has proven to be effective and efficient.